Clinical and functional outcome of minimally invasive transforaminal lumbar interbody fusion in single segment lumbar spinal disease: a prospective observational study - Shreyas, Cheemullu Shivashankar; Tak, Mahendra Singh; Bhati, Mahesh; Suthar, Lakshit (International Journal of Research in Medical Sciences, 2025)
Background: Low back pain is the most common cause of work-related disability, which can be commonly caused by lumbar disc herniation, lumbar spinal stenosis, lumbar instability, and lumbar spondylolisthesis. Generally, treated conservatively, requiring surgical intervention when the effect of non-surgical management is poor or when symptoms of severe nerve damage occur. In the past decade, mainstream spinal surgery has been open surgery. Many studies have reported that minimally invasive TLIF provides equal or better results compared to open surgery. However there is very limited research on their clinical and functional outcome which is assessed in this study. Methods: This was a prospective observational study conducted in a tertiary care hospital for one year. Patients who underwent MIS TLIF were assessed for clinical and functional outcome with ODI and VAS score pre operative and post operative at one year. Blood loss and surgical duration was also calculated. Patients aged 20-55 with lower back pain and /or neurogenic deficit that originated from single level lumbar degenerative disease were included. Those with new or old spinal fractures, previous spinal surgery and patients with medical condition requiring intensive medical therapy were excluded. Results: The mean pre-operative VAS score was 7.64±0.95, which significantly decreased to 2.28±0.89 post-operatively, with a p-value of 0.000, indicating a statistically significant reduction in pain levels. Similarly, mean pre-operative ODI was 68.72±6.63, which decreased to 19.3.0±2.82 post-operatively, with a p value of 0.000, demonstrating significant improvement. Conclusions: Our results suggest that MIS TLIF procedure has good clinical and functional outcome (p value <0.05) in terms of ODI and VAS Score and thus can be considered an ideal advancement in surgical procedure.